Engaging Youth in the Bipolar Youth Action Project: Community-Based Participatory Research - Lapadat, Laura (J Particip Med, 2020)
BACKGROUND: We describe the methodological dimensions of community-based participatory research through a description of study design, youth engagement, and methods/processes in the cocreation of knowledge within a Canadian study, the Bipolar Youth Action Project. This collaborative partnership—carried out by a team composed of academic, community, and youth partners—was designed to investigate self-management and wellness strategies for young adults living with bipolar disorder. OBJECTIVE: The aim is to describe the opportunities and challenges of this collaboration and to reflect upon the process of involving youth with bipolar disorder in health research that concerns them, and share lessons learned. METHODS: The project was conducted in multiple phases over 2 years: (1) grant-writing, with youth contributing to the process; (2) recruitment, in which 12 youth were selected and trained to help shape and conduct two research forums; (3) the first research forum, where more youth were consulted about the strategies they apply to stay well (self-management strategies); (4) data analysis of Forum I findings; (5) research Forum II, which consulted youth with bipolar disorder about knowledge translation of Forum I findings; and (6) data analysis of Forum II findings. Youth peer researchers with bipolar disorder were involved in a significant capacity at every stage in the process. RESULTS: Of the initial 12 youth peer researchers, 7 remained on the project from the recruitment phase until the project ended. They collaborated in the creation of two youth research forums that consulted youth with bipolar disorder on their self-management strategies. CONCLUSIONS: This article shares what was learned from the process of partnering with youth with bipolar disorder in a community-based participatory research study.